Stroke-like presentation of Giant Cell Arteritis - Skoczyński, Marcin Paweł; Micał, Wojciech; Tarkowski, Piotr (Journal of Education, Health and Sport, 2019)
Stroke is a severe medical condition, which should be diagnosed ant treated rapidly. During imaging diagnostics atypical appearance of vessels may suggest other than thrombotic occlusion. Circumferential vascular stenosis is typical for giant cell arteritis, which should be considered as a differential diagnosis and treated with corticosteroids.